2018
DOI: 10.1007/s00423-018-1653-6
|View full text |Cite
|
Sign up to set email alerts
|

Extended pancreatectomy as defined by the ISGPS: useful in selected cases of pancreatic cancer but invaluable in other complex pancreatic tumors

Abstract: Extended pancreatectomies resulted in similar peri-operative morbidity and mortality compared to standard pancreatectomies. Although the survival of patients undergoing these complex procedures is inferior to standard pancreatectomies, they should be undertaken not only in selected cases of pancreatic cancer but even more so in other complex pancreatic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…1). As the unit was evolving into a specialised centre with increasing number of cases, there was gradual incorporation of neoadjuvant protocols, superior mesenteric artery (SMA) first approach, multivisceral and vascular resections in routine practice [25][26][27][28][29][30]. Period B also witnessed the widest and biggest expansion of surgical oncology residency programme for speciality trainees across India.…”
Section: Discussionmentioning
confidence: 99%
“…1). As the unit was evolving into a specialised centre with increasing number of cases, there was gradual incorporation of neoadjuvant protocols, superior mesenteric artery (SMA) first approach, multivisceral and vascular resections in routine practice [25][26][27][28][29][30]. Period B also witnessed the widest and biggest expansion of surgical oncology residency programme for speciality trainees across India.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that patient with extended resections had significantly high rates of morbidity and mortality after pancreatic surgery. 20,[37][38][39] With regards to arterial resection, data are debatable and tend to consider this procedure for selected cases in expert centres. [40][41][42] Perinel et al showed that in highly selected patients, arterial resection can be carried out during PD with an appropriate and sustained arterial reconstruction technique.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with avoidable deaths tended to occur at an earlier stage, to have more blood loss, to require longer operative time, to show more surgical complications and patients were more likely to die within 30 days after pancreatectomy. It is obvious that patient with extended resections had significantly high rates of morbidity and mortality after pancreatic surgery 20,37–39 . With regards to arterial resection, data are debatable and tend to consider this procedure for selected cases in expert centres 40–42 .…”
Section: Discussionmentioning
confidence: 99%
“…Anterior and posterior RAMPS were defined as reported by Strasberg et al [5][6][7] Extended resections were defined as en-bloc resection of a neighboring organ such as the stomach or colon. 18 Postoperative course was classified prospectively at discharge, according to the Clavien-Dindo Classification (CDC). 19 Complications graded >IIIa, were considered severe.…”
Section: Thismentioning
confidence: 99%